Analisis Faktor-faktor yang mempengaruhi Minat Berinvestasi Mahasiswa Di Universitas Palangka Raya - Ramadaniyah, Niyah; Christa, Usup Riassy; Nugroho, Sanjayanto; Mahrita, Ani (Jurnal Salingka Nagari, 2025)
This study aims to identify the factors that influence the Investment Interest of Students at Palangka Raya University. The population in this study were 6,753 Palangka Raya University students and a sample of 378 student obtained using the Proportionate Stratified Random Sampling technique. The data will be analyzed using desciptive analysis. The results of the analysis show that the factors of Information Technology progress and Return, as well as digital literacy factors are factors that influence the investment interest of student at Palangka Raya Univercsity. And the results of the analysis show that Risk factors do not affact the investment interest of students at palangka raya university.